2021
DOI: 10.3390/cancers13164043
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance and the Role of Guanylate-Binding Protein 5 in Oral Squamous Cell Carcinoma

Abstract: Guanylate binding protein 5 (GBP5) is the interferon (IFN)-inducible subfamily of guanosine triphosphatases (GTPases) and is involved in pathogen defense. However, the role played by GBP5 in cancer development, especially in oral squamous cell carcinoma (OSCC), is still unknown. Herein, next-generation sequencing analysis showed that the gene expression levels of GBP5 were significantly higher in OSCC tissues compared with those found in corresponding tumor adjacent normal tissues (CTAN) from two pairs of OSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Except for these genes, CASP8, GBP5 and LUCAT1 have been reported to play multiple roles in numerous cancer types, such as head and neck cancer, oral squamous cell carcinoma, esophageal squamous cell carcinoma, colorectal cancer and HCC. 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 For example, recent studies suggested that CASP8 is involved in autophagy‐related apoptosis and can be used as a prognostic marker of HCC together with other molecules, 52 , 53 and GBP5 can be used as a prognostic biomarker of HCC together with other genes, and it is closely related to immune characteristics. 54 Furthermore, LUCAT1 was reported to affecting the proliferation, migration and invasion processes of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Except for these genes, CASP8, GBP5 and LUCAT1 have been reported to play multiple roles in numerous cancer types, such as head and neck cancer, oral squamous cell carcinoma, esophageal squamous cell carcinoma, colorectal cancer and HCC. 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 For example, recent studies suggested that CASP8 is involved in autophagy‐related apoptosis and can be used as a prognostic marker of HCC together with other molecules, 52 , 53 and GBP5 can be used as a prognostic biomarker of HCC together with other genes, and it is closely related to immune characteristics. 54 Furthermore, LUCAT1 was reported to affecting the proliferation, migration and invasion processes of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of GBP5 was scored semi‐quantitatively based on the staining intensity and extent of cancer and stromal cells, as previously reported. 27 , 28 The staining intensity scores were categorized as negative (0), mild (1), moderate (2), strong (3), while the staining extent as <5% (0), 5 to <25% (1), 25 to <50% (2), 50% to <75% (3), ≥ 75% (4). The total intensity and extent of staining scores in tumor and stromal cells were defined as the GBP5 tumor and GBP5 stromal scores (ranging from 0 to 7), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The nucleotide sequences of TMEM211 primer (Forward: 5′-GCCTCCTCCATGTATTATGGTG-3′; Reverse: 5′-CCTTGGACCTTGGTTGTGTG-3′) were used in this study. More detailed procedures were described in a previous study [ 39 ].…”
Section: Methodsmentioning
confidence: 99%